Extracellular host DNA contributes to pathogenic biofilm formation during periodontitis - Slobodianyk-Kolomoiets, Mariana; Khlebas, Svitlana; Mazur, Iryna; Rudnieva, Kateryna; Potochilova, Viktoria; Iungin, Olga; Kamyshnyi, Olexandr; Kamyshna, Iryna; Potters, Geert; Spiers, Andrew J.; Moshynets, Olena (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Periodontal diseases are known to be associated with polymicrobial biofilms and inflammasome activation. A deeper understanding of the subgingival cytological (micro) landscape, the role of extracellular DNA (eDNA) during periodontitis, and contribution of the host immune eDNA to inflammasome persistence, may improve our understanding of the mechanisms underlaying severe forms of periodontitis. Methods In this work, subgingival biolfilms developing on biologically neutral polyethylene terephthalate films placed in gingival cavities of patients with chronic periodontitis were investigated by confocal laser scanning microscopy (CLSM). This allowed examination of realistic cytological landscapes and visualization of extracellular polymeric substances (EPS) including amyloids, total proteins, carbohydrates and eDNA, as well as comparison with several single-strain in vitro model biofilms produced by oral pathogens such as Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus gordonii, S. sanguinis and S. mitis. Fluorescence in situ hybridization (FISH) analysis was also used to identify eDNA derived from eubacteria, streptococci and members of the Bacteroides–Porphyromonas–Prevotella (BPP) group associated with periodontitis. Results Analysis of subgingival biofilm EPS revealed low levels of amyloids and high levels of eDNA which appears to be the main matrix component. However, bacterial eDNA contributed less than a third of the total eDNA observed, suggesting that host-derived eDNA released in neutrophil extracellular traps may be of more importance in the development of biofilms causing periodontitis. Discussion eDNA derived from host immunocompetent cells activated at the onset of periodontitis may therefore be a major driver of bacterial persistence and pathogenesis.